UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU IPS DALAM PROSES PEMBELAJARAN - Patrisia Heni Jogo; Muhammad Fitri; Abdul Kholiq; Anggreni Kaweda Madiku (STKIP Persada Khatulistiwa Sintang, 2022)
Professional competence is a learning ability related to mastery of the material broadly and deeply. However, this is not in accordance with the observations of social studies teachers and junior high school principals that teachers experience difficulties in presenting economic material, limited sources of teaching materials and teaching media, and the method used is still limited to the KTSP method. This study aims to reveal the professional competence of social studies subject teachers in the learning process. The method used is a qualitative research with the subject of this research are social studies subject teachers and principals. Data collection techniques were carried out through interviews, observation and documentation. While the data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of the study reveal that social studies teachers have not fully met the professional competence of teachers. Efforts are being made to overcome this by involving social studies teachers in MGMP activities, seminars, training and Technical Guidance (Bimtek). Meanwhile, efforts to improve the professionalism of school principals by following supervision.